Grey Relational Analysis of the Determinants of Direct Sales of Food Crops in India - Sahu, Kishor Chandra; Ramana Murthy, M. V.; Sasidhar, B. (Arthshastra Indian Journal of Economics & Research, 2019)
To achieve higher levels of sales, the agricultural crop farms depend exclusively on the direct-to-consumer channels. Many existing research studies discussed and answered various issues on the production and human consumption of the food crops. Also, several studies discussed the factors affecting the direct sales of the food crops. However, it is very much essential to calculate the expectations on the direct sales from the farmers' perspective. This paper explored the factors which influence the direct sales of the food crops by following the exploratory factor analysis (EFA). The study also proposed a prioritization methodology of those factors that affected the direct sales of food crops in the Indian context based on a survey administered on the local farmers who produce food crops. We followed the grey relational analysis for arranging the scale items for the production variables in ascending or descending order. The findings of the study will allow the farmers, researchers, and managers to explore the relationship among the items in terms of the degree of importance to each other.